Model Dialog Agama George Lindbeck: Sumbangan bagi Dialog Agama-Agama di Indonesia - Lesmana, Iknasius Bayu (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
The main concerns of the postmodern Christian theological movement is to return to a special Christian identity and be clear in assessing the peculiarities of other religions. This study aims to describe George Lindbeck's theory about interreligious dialogue. The method used is literature study. Through this study, it can be understood that George Lindbeck was a Lutheran theologian who was sensitive to the development of postmodern Christian theology. His new approach is known as the cultural-linguistic approach. Cultural-linguistic theory invites everyone to be able to have a casual dialogue, according to their respective views, exchange of experience, learn, and cooperate. George Lindbeck's theological ideas and dialogues are relevant for Indonesians who have cultural and religious diversity. The main task of a Christian in dialogue is to explain himself as a Christian. In addition, a Christian must also be willing to give himself to learn the language game that his dialogue partner has. This way of dialogue can minimize the doctrinal debate that has been going on in Indonesia.AbstrakPerhatian utama gerakan teologi Kristen postmodern adalah kembali kepada identitas khusus Kristiani dan jernih dalam menilai kekhasan agama-agama lain. Penelitian ini bertujuan untuk mendeskripsikan teori George Lindbeck mengenai dialog agama-agama. metode yang digunakan adalah studi pustaka. Melalui penelitian ini, dapat dipahami bahwa George Lindbeck adalah teolog Lutheran yang peka akan perkembangan teologi Kristen postmodern. Pendekatan barunya dikenal sebagai pendekatan kultural-linguistik. Teori kultural-linguistik mengundang semua orang untuk dapat melakukan dialog secara santai, sesuai dengan pandangan masing-masing, saling bertukar pengalaman, belajar, dan bekerja sama. Gagasan teologi dan dialog George Lindbeck ini relevan bagi bangsa Indonesia yang memiliki keanekaragaman kultural dan agama. Tugas utama seorang Kristiani yang sedang berdialog itu adalah menjelaskan dirinya sendiri sebagai umat Kristiani. Seorang Kristiani juga harus mau memberi diri untuk mempelajari language game yang dimiliki mitra dialognya. Cara dialog ini dapat meminimalisir perdebatan doktrin yang selama ini terjadi di Indonesia.